Mangrove Ecosystem Services in Mitigation for Mollusca Communities in Lembar Sheet District, West Lombok Regency - Sekar Partiwi; Agil Al Idrus; Rizal Umami (Jurnal Biologi Tropis, 2023)
Mangroves have an important role in mitigation and a significant contribution to the wealth of macrofauna. The success of mangrove management has significantly affected the diversity of macrofauna which are associated biota. The research objectives were to investigate the composition of mangroves and mollusc communities, the ecological conditions of the waters, and evidence of mangrove ecosystem services in mitigation. The research data sources are faunal, ecological, and social data. The research method uses purposive sampling and data analysis using descriptive statistics. The results showed that 7 mangrove species were found in the Cemare mangrove area. Avicennia marina, Bruguiera gymnorriza, Ceriops tagal, Rhizophora apiculata, Rhizophora mucronata, Rhizophora stylosa, and Sonnetaria alba. The dominant mangroves were Rhizopora stylosa (201 ind/Ha) and Rhizopora apiculata (146 ind/Ha). Meanwhile, the highest abundance of mollusc species was obtained by Cerithidea cingulate (38.94%) and Nerita undata (29.20%) from the gastropod class, while from the Bivalvia class, Anadara grandis (36.07%) and Anadara granosa (19.67%) were found). The condition of the aquatic environment at the research site is still within the tolerance range required for the growth and development of mollusk species. Furthermore, the majority of respondents know or are aware that mangroves have an ecological function (habitat/habitat for animals), an economic function (a livelihood location), a physical mitigation function (abrasion resistance), a non-physical mitigation function (reducing environmental heat) Good category. These results indicate that efforts need to be made to increase mangrove revegetation, given its significant benefits in mitigation.